Respiratory motion management techniques for radiotherapy of thoracic and upper abdominal tumors at King Chulalongkorn Memorial Hospital - Wisetrinthong, Metinee; Kanphet, Jaruek (The Thai Journal of Radiological Technology, 2024)
The radiation therapy precisely targets high doses of radiation and minimizes the risk of radiation exposure to neighboring healthy tissue of the modern radiotherapy machines and treatment planning techniques has been well demonstrated. However, it presents unique challenges for accurate planning and delivery especially in the lungs and upper abdomen where respiratory motion can be significantly confounding accurate targeting and avoidance of normal tissues. In this paper, we explain how to manage breathing motions in the field of division of Radiation Oncology, Department of Radiotherapy, King Chulalongkorn Memorial Hospital to reduce the effects of breathing motion, which will allow precise irradiation and can reduce the amount of radiation on Organs at risk and normal tissues, which will result in fewer side effects from radiation